Reliability Comparison of High Performance Computing between Single Thread Loop and Multiple Thread Loop using Java-Based Programming at Fingerprint Data Processing - Arief Ginanjar; Kusmaya Kusmaya (JURNAL SISFOTEK GLOBAL, 2022)
High Performance Computing is one of the mechanisms in the programming family with a focus on increasing high performance in any programming environment, especially programming languages that use virtual machine environments such as C/C++, Java and Python. several sub-clusters of information technology such as Big Data, Data Warehouse, Business Intelligence and Artificial Intelligence, the use of HPC is widely applied in sophisticated computer machines that have enterprise data processing capabilities. This research was conducted to compare the ability of HPC with algorithms or java programming techniques in data processing that uses a lot of threads when implemented in ordinary computers used in everyday life, the term java programming technique that uses one thread is called Single Thread Loop then when using multiple threads is called Multiple Thread Loop. Due this comparison between sequential and parallel process so this research try to compare between Single Thread Loop and Multiple Thread Loop in Java Programming. The minimum requirement operating system is to use the MS Windows 7 or 10 and a Unix-based OS using an Intel i5 or i7 processor and use a minimum of 16 GB of RAM.